L’évolution des pratiques agricoles face aux enjeux de la qualité de l’eau : le bassin de l’Oudon (France) - François Laurent (Territoire en Mouvement)
The protection of water supply and aquatic environments are threatened by agricultural non-point source pollution in the northwest of France. Management policies of water resources are based on the participation of farmers to adapt solutions to territories. Indeed, if regulation is necessary, is not sufficient to achieve a satisfactory quality in many watersheds polluted by nitrates, phosphorus and pesticides. Membership of farmers in territorial projects of restoration of water quality is required. The watershed of the Oudon (1 480 km²), located in the Pays de la Loire region, is mainly oriented to dairy cattle farming. Farmers are actively involved in a Local Water Commission of the Water Management Plan to find and develop actions. The analysis of the technical, economic and cultural dimensions is use to better understand the complexity of farmers’ behaviour in front of pollutions and highlights the levers and barriers to disseminate best management practices.